2021
DOI: 10.1080/15592324.2021.1970448
|View full text |Cite
|
Sign up to set email alerts
|

Plants make smart decisions in complex environments

Abstract: This review proposes that plants make smart decision and encourages scientists to formulate and test hypotheses about plant's decisions as an option to investigate complex phenomena that are hardly explained through the predominant mechanistic approach. Three physiological processes (seed germination and seedling emergence, abortion of reproductive structures, and regulation of photosynthesis) are discussed to illustrate the plant's ability to make decisions from three different perspectives. It is proposed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Although Dener et al (2016) demonstrated that their plants are sensitive to nutrient variability over time and hence are risk sensitive, we do not consider them to have demonstrated optimal risk sensitivity in plants. The suggestion that pea plants make optimal decisions about risk (Karban & Orrock, 2018;Severino, 2021;Lee, Segundo-Ortin & Calvo, 2023) and hence are more rational than animals (Schmid, 2016) cannot be accepted.…”
Section: Generalitymentioning
confidence: 99%
“…Although Dener et al (2016) demonstrated that their plants are sensitive to nutrient variability over time and hence are risk sensitive, we do not consider them to have demonstrated optimal risk sensitivity in plants. The suggestion that pea plants make optimal decisions about risk (Karban & Orrock, 2018;Severino, 2021;Lee, Segundo-Ortin & Calvo, 2023) and hence are more rational than animals (Schmid, 2016) cannot be accepted.…”
Section: Generalitymentioning
confidence: 99%
“…As regards decision-making processes, there is a growing body of evidence to suggest that plants have the ability to learn, to process information, to communicate, to reach decisions, and in general to exhibit behavior that could be considered cognitive (reviewed in Severino, 2021). For instance, researchers have found that plants can "remember" a previous exposure to stress and respond more effectively to that same stressor in the future (Galviz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some scientists argue that the behaviors observed in plants are better explained by simpler mechanisms, such as chemical or mechanical responses, rather than true cognitive processes. To avoid such controversy, Severino (2021) makes the case for experimental approaches. A recent experimental approach for the study of decision-making processes in germinating seedlings has incorporated two tools used in decision theory: the use of a limited budget and of conflict-of interest scenarios (Kalbfuß et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations